2020
DOI: 10.1002/wat2.1422
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the state of research data publication in hydrology: A perspective from the Consortium of Universities for the Advancement of Hydrologic Science, Incorporated

Abstract: Many have argued that datasets resulting from scientific research should be part of the scholarly record as first class research products. Data sharing mandates from funding agencies and scientific journal publishers along with calls from the scientific community to better support transparency and reproducibility of scientific research have increased demand for tools and support for publishing datasets. Hydrology domain-specific data publication services have been developed alongside more general purpose and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…To better support transparency and reproducibility of scientific research, data and codes of scientific research should be part of the scholarly work, and must be considered and treated as a first-class research product ( Horsburgh et al, 2020 ). We follow the FAIR Guiding Principles for scientific data management and stewardship ( Wilkinson et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…To better support transparency and reproducibility of scientific research, data and codes of scientific research should be part of the scholarly work, and must be considered and treated as a first-class research product ( Horsburgh et al, 2020 ). We follow the FAIR Guiding Principles for scientific data management and stewardship ( Wilkinson et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…As summarized by Attard et al (2015), factors that can limit data discoverability in open portals include low metadata quality, simplistic search functionality, lack of ways to explore datasets to determine their relevance. Another factor cited in the case of HIS is the need for there to be a critical mass of data big enough to improve the chances of a scientist discovering data that they want to use and to keep using the repository (Horsburgh et al, 2020).…”
Section: Barriers To the Use Of Open Data Products By End Users And S...mentioning
confidence: 99%
“…There is another barrier that lies at the intersection of open data and open science: the lack of rewards and incentives, which reduces the likelihood that a researcher will expend valuable time to work through the costs and risks of making data open (Bierer et al, 2017;Borgman, 2007Borgman, , 2012Burgelman et al, 2019;Saenen et al, 2019). In the context of water data, Horsburgh et al (2020) have identified lack of rewards and incentives for researchers as a key challenge inhibiting the publication of hydrologic data in open repositories. This can be viewed as part of larger problem of data sharing in the research community more broadly (Borgman, 2012;Flint et al, 2017;Wallis et al, 2013).…”
Section: Lack Of Rewards and Incentivesmentioning
confidence: 99%
See 2 more Smart Citations